(untitled) (Bangladesh Journal of Infectious Diseases, 2017)
Background: Campylobacter jejuni infected diarrhoea can occur in different socioeconomic condition among the children under 5 years. Objective: The purpose of the present study was to see the socioeconomic condition among the Campylobacter jejuni infected diarrhoea children under 5 years of age. Methodology: This was a cross sectional study conducted in the Department of Microbiology at Banghabanhdhu Sheikh Mujib Medical University (BSMMU), Dhaka from July 2007 to June 2008 for a period of 1(one) year. All the diarrhoeal samples were collected from outdoor unit of ICDDR,B. Children up-to 5 years of age with acute diarrhoea with or without blood and mucous associated with either fever or abdominal pain or both were included as study population. Stool samples were collected from all diarrhoeal children in a sterile collection pot. Detection of Campylobacter antigen was performed from stool samples. The inoculated selective media in the candle jar were incubated at 42°C (microaerophilic condition) for 48 hours which is favorable for the growth of the organism. With the above criteria it is confirmed as Campylobacter, further identification of suspected Campylobacter jejuni and Campylobacter coli was confirmed by standard test. Result: Two hundred and seventeen children up-to 5 years of age who were suffering from acute diarrhoea were studied to assess the rate of infection by Campylobacter jejuni and Campylobacter coli as an enteric pathogen. Among 217 diarrhoeal children, Campylobacter were isolated from 28(12.9%) cases. Isolation rate of Campylobacter was 19.3% in below 1 year of age group and 5.8% was above 1 year of age group (p<0.003). Out of 217 study patients 141 were male and 76 were female and the isolation rate of Campylobacter were 20(14.2%) from male and 8(10.5%) from female respectively (p>0.05). About 50.0% Campylobacter positive patients were belong to lower class and 35.7% were in middle class. Conclusion: In conclusion Campylobacter jejuni infected diarrhoea children under 5 years of age are mostly below 1 year of age with a predominance of male. Bangladesh Journal of Infectious Disease 2015;2(2):33-36